2021
DOI: 10.1111/exd.14351
|View full text |Cite
|
Sign up to set email alerts
|

Innate lymphoid cells in peripheral blood of patients with American Cutaneous Leishmaniasis

Abstract: Innate lymphoid cells (ILCs) are classified by the expression of specific transcription factors: ILC1 depending on T‐bet for IFN‐γ production; ILC2 depending on GATA3 for IL‐5 and IL‐13; and ILC3 depending on ROR‐γτ and AHR for IL‐17 and IL‐22. This study aimed to determine circulating ILCs in 23 patients with localized (LCL) = 7, mucocutaneous (MCL) = 10, intermediate (ICL) = 3 and diffuse (DCL) = 3 cutaneous leishmaniasis and 17 healthy controls from endemic area (EC) = 9 and non‐endemic area (HC) = 8. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…For example, LCL (Localized Cutaneous Leishmaniasis) has a higher presence of both ILC1 and ILC3 responses. Therefore, it may be responsible for promoting a Th1 response, which can help control the infection [65]. Specifically, in LCL patients, a unique subtype of ILC1 that requires T-bet for differentiation can produce significant amounts of IFN-γ and TNF-α when exposed to cytokines from infected cells, resulting in a more robust Th1 response and consequent classical macrophage activation, as previously observed in inflammatory bowel disease (IBD) and infection-induced colitis [66,67].…”
Section: Ilcsmentioning
confidence: 76%
See 2 more Smart Citations
“…For example, LCL (Localized Cutaneous Leishmaniasis) has a higher presence of both ILC1 and ILC3 responses. Therefore, it may be responsible for promoting a Th1 response, which can help control the infection [65]. Specifically, in LCL patients, a unique subtype of ILC1 that requires T-bet for differentiation can produce significant amounts of IFN-γ and TNF-α when exposed to cytokines from infected cells, resulting in a more robust Th1 response and consequent classical macrophage activation, as previously observed in inflammatory bowel disease (IBD) and infection-induced colitis [66,67].…”
Section: Ilcsmentioning
confidence: 76%
“…A study by Rodríguez et al (2021) showed the variability of different proportions of ILC phenotypes in other forms of Leishmaniasis. For example, LCL (Localized Cutaneous Leishmaniasis) has a higher presence of both ILC1 and ILC3 responses.…”
Section: Ilcsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rodriguez et al studied the distribution of ILC1, ILC2 and ILC3 in the peripheral blood of Venezuelan patients with localized (LCL; n = 7), intermediate type (ICL; n = 3) or diffuse cutaneous leishmaniasis (DCL; n = 3) or with mucocutaneous leishmaniasis (MCL; n = 10) as compared to healthy controls ( n = 17). Although the underlying parasite species was not reported and the number of analyzed patients was small, the authors obtained evidence that ILC1 were more frequent in LCL patients, whereas ILC2 were the predominant ILC type in DCL patients, who exhibit T cell anergy and disseminated disease [ 43 ]. Singh et al reported that IL-17A-producing ILC3 were enriched in the skin lesions of C57BL/6 mice at day 7 of infection with L. major .…”
Section: Discussionmentioning
confidence: 99%
“…In a parabiotic mice model of inhibiting commensal bacteria with antibiotics, resting ILC2s residing in intestinal lamina propria are activated by IL-33 or helminths into iILC2s, which migrate to various extraintestinal tissues through sphingosine 1-phosphate (S1P)-mediated chemotaxis to participate in anti-helminth defense and tissue repair (18). hILC2s were previously considered to be exclusively tissue-resident, but this couldn't explain the increased abundance of ILC2s and other ILC subsets in peripheral blood of American cutaneous leishmaniasis patients compared with healthy volunteers (19). The latest research shows that, CD45RO + ILC2s are derived from resting CD45RA + ILC2s in airway inflammation and are regarded as human equivalent of the iILC2 subset (20).…”
Section: Ilc2 Differentiation and Migrationmentioning
confidence: 99%